2013
DOI: 10.1371/journal.pone.0080892
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Relaxation Mechanisms and Oxidative Stress Are Restored by Atorvastatin Therapy in Ovariectomized Rats

Abstract: The studies on hormone replacement therapy (HRT) in females with estrogen deficiency are not conclusive. Thus, non-estrogen therapies, such as atorvastatin (ATO), could be new strategies to substitute or complement HRT. This study evaluated the effects of ATO on mesenteric vascular bed (MVB) function from ovariectomized (OVX) female rats. Female rats were divided into control SHAM, OVX, and OVX treated with 17β-estradiol (EST) or ATO groups. The MVB reactivity was determined in organ chambers, vascular oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 73 publications
2
7
0
Order By: Relevance
“…Indeed, results from our laboratory indicate that the main endothelial mediator responsible for regulating the coronary vascular tone (represented by the baseline CPP) is the NO in both Wistar and SHR rats (Santos et al, 2004, 2010, 2016). Therefore, ovariectomy leads to damages on the endothelial function, as previously showed by our study group (Borgo et al, 2011; Caliman et al, 2013; Claudio et al, 2013; Oliveira et al, 2014; Lamas et al, 2015); impairing thus, the preventive/therapeutic effects from the PHE on the baseline CPP values in the OVX-PHE group. Another suggestion is that the beneficial effects from the treatment are probably dependent on circulating estrogen levels in the blood, since we observed that animals with normal estrogen levels (Sham) showed the benefits generated by the treatment.…”
Section: Discussionsupporting
confidence: 70%
“…Indeed, results from our laboratory indicate that the main endothelial mediator responsible for regulating the coronary vascular tone (represented by the baseline CPP) is the NO in both Wistar and SHR rats (Santos et al, 2004, 2010, 2016). Therefore, ovariectomy leads to damages on the endothelial function, as previously showed by our study group (Borgo et al, 2011; Caliman et al, 2013; Claudio et al, 2013; Oliveira et al, 2014; Lamas et al, 2015); impairing thus, the preventive/therapeutic effects from the PHE on the baseline CPP values in the OVX-PHE group. Another suggestion is that the beneficial effects from the treatment are probably dependent on circulating estrogen levels in the blood, since we observed that animals with normal estrogen levels (Sham) showed the benefits generated by the treatment.…”
Section: Discussionsupporting
confidence: 70%
“…39 The product of eNOS activity, NO, is an endogenous vasodilator 40 that preserves endothelial function and homeostasis and thus protects against endothelial dysfunction in diseases such as hypertension, heart failure, diabetes and atherosclerosis, 41 all of which are generally less prevalent in women than in men. 42 ERs are also associated with protective cardiovascular effects 43 and estrogens regulate the expression of eNOS and/or NO-production 44 in rat tissues 45, 46 and human endothelial cell lines. 29, 30 In agreement, we find that lungs and aortas from female mice express higher levels of eNOS, with concomitant higher baseline phosphorylation in Ser 1177 than the male or ovariectomized counterparts, and that estradiol increases eNOS expression in mouse endothelial cells (E Fig 3, B in the online repository).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity or weight gain may lead to cardiac apoptosis [43,44,45,46], but it is still unclear whether the increased cardiac apoptotic activity is partially due to the deleterious factor of weight gain after an ovariectomy. Moreover, the coexistence and independence of ovariectomy and hypertension share many of the same or different disease processes and risk factors, such as weight change [42], increased inflammation [47], oxidative stress [48,49], renin-angiotensin system activity [6,26] and heart and renal changes [50]. This implies that other factors involved in these changes and further studies are required to evaluate these issues.…”
Section: Discussionmentioning
confidence: 99%